A Transition Discovered in the Subcritical Regime of 1A 0535+262 - Hua Xiao; Long Ji (The Astrophysical Journal, 2024)
We present NICER observations of the accreting X-ray pulsar 1A 0535+262 during its faint state (≲6 × 10 ^36 erg s ^−1 ), observed in several type I and type II outbursts. We discovered a transition of temporal and spectral properties around the luminosity L _t = 3.3 × 10 ^35 erg s ^−1 , below which spectra are relatively soft and the pulse profiles have only a narrow peak. The spectra are harder and a secondary hump gradually appears in the pulse profiles when L ≳ L _t . We discuss possible physical mechanisms for this transition, including different Comptonization seed photons, the disappearance of gas shocks on the neutron star surface, and the combination of plasma and vacuum polarization effects.